Design of Telecom Service Network Infrastructure and Analysis of Key Tecbnologies - Gang Lu; Zhe Wang; Honghui Ou; Hui Wang (Dianxin kexue)
Telecom network is software and hardware and network environment to realize and safeguard the service， because of the changes of industrial environment and development of the hardware and software technology， telecommunication network need to upgrade and reconstruction. The demand, technology and architecture evolution of telecom network were described, and the architecture of the service network was proposed. Key technologies of software defined layer were analyzed especially. The development prospects of the service network were discussed.